2016
DOI: 10.1111/1471-0528.13901
|View full text |Cite
|
Sign up to set email alerts
|

Association between parity and fistula location in women with obstetric fistula: a multivariate regression analysis

Abstract: Objective To compare primiparous and multiparous women who develop obstetric fistula (OF) and to assess predictors of fistula location Design Cross-sectional study Setting Fistula Care Center at Bwaila Hospital, Lilongwe, Malawi Population Women with OF who presented between September 2011 and July 2014 with a complete obstetric history were eligible for the study. Methods Women with OF were surveyed for their obstetric history. Women were classified as multiparous if prior vaginal or cesarean delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
4
7
0
Order By: Relevance
“…rds Over 2/3 of the women were multiparous, and had experienced prolonged labour of varying degree (Table 1). Similar findings were noted in other 22,34 settings.…”
Section: Resultssupporting
confidence: 89%
“…rds Over 2/3 of the women were multiparous, and had experienced prolonged labour of varying degree (Table 1). Similar findings were noted in other 22,34 settings.…”
Section: Resultssupporting
confidence: 89%
“…In our study, grandmultiparity, repeat CS, CS performed by an intern doctor and CS done at a lower health facility (Health Centre IV) were risk factors for iatrogenic stula from cesarean section. Our nding of high parity is in correlation with other studies where the odds of iatrogenic stula increased with rising parity [15,24]. This may be because multiparous women have a thinner lower segment which is more likely to get tears extending to the urinary bladder during cesarean delivery and if unnoticed results into stula (14).…”
Section: Resultssupporting
confidence: 88%
“…Previous studies from other countries have found primiparity, as well as five or more births as a risk factor for obstetric fistula development. 2, 13 The pregnancy in which the obstetric fistula occurred cannot be ascertained in this study but the association of multiparity could be explained by change in pelvic structure due to nutritional factors, trauma, deformity, malpresentations, and increase in birth weight with each pregnancy. 2 In our study several socio-economic factors were associated with obstetric fistula including wealth index, a woman and her husband's education level, healthcare decision making role, and a woman's employment status.…”
Section: Discussionmentioning
confidence: 83%
“…Our study found that multiparous women were more likely to report suffering from obstetric fistula than nulliparous or primiparous women, and the prevalence increased with increasing number of pregnancies. Previous studies from other countries have found primiparity, as well as five or more births as a risk factor for obstetric fistula development 2,13 2 …”
Section: Discussionmentioning
confidence: 96%